A coaxiality measurement model based on multi-systematic errors separation for turbine shaft. (December 2021) - Liu, Yongmeng; Li, Ruirui; Sun, Chuanzhi; Mei, Yingjie; Wang, Xiaoming; Tan, Jiubin; Wang, Hongye
Highlights: This paper proposed a seven systematic errors measurement model. The measurement model can improve the accuracy of coaxiality. This paper designed an unequal interval 3D morphological filter. The filter operation can improve the accuracy of coaxiality. Abstract: Aiming at the problem that the systematic errors affect the coaxiality measurement accuracy of turbine shaft, this paper proposes a seven systematic errors measurement model which considers eccentricity, workpiece tilt, probe offset, probe radius, probe strut tilt, horizontal and vertical guide rail tilt. Considering the unequal interval distribution of sample angle, this paper designed an unequal interval 3D morphological filter is designed for data processing based on the actual sample angle distribution. The effectiveness of the seven systematic errors profile measurement model and unequal interval 3D morphological filter is studied by simulation and experiment. The results show that the coaxiality measurement accuracy of the unequal interval 3D morphological filter is improved by 2.17 μm compared with the equal interval filter, and the accuracy of the seven systematic errors measurement model is improved by 2.79 μm compared with the five systematic errors measurement model when the error level is E5.